A Randomized Study of the Effect of Mifepristone Alone or in Conjunction with Ethinyl Estradiol on Ovarian Function in Women Using the Etonogestrel-Releasing Subdermal Implant, Implanon® - Croxatto -Avoni, H (2011)
Background: Mifepristone alone or in combination with ethinyl estradiol (EE) can effectively stop an episode of uterine bleeding in women using the etonogestrel-releasing contraceptive implant, Implanon® but could impair contraceptive efficacy. Aim: To examine the effects of administration of mifepristone alone or with EE on ovarian function and cervical mucus consistency in women using Implanon. Study Design: Women using Implanon were randomized to mifepristone 25 mg twice daily on day 1 plus placebo 1 daily for 4 days or plus EE 20 mcg daily for days 2-5. Measurements of serum estradiol (E 2), progesterone (P 4), luteinizing hormone (LH), follicle-stimulating hormone (FSH), cervical mucus examination and maximal follicle size (by vaginal ultrasound) were carried out at various times. Results: Following mifepristone intake, there was a dramatic increase in E 2 levels ranging from 543 to 1183 pmol/L (p=.000), which was not correlated with maximal follicle size or preceded by LH or FSH increase. The increase in E 2 triggered an LH increase resulting in development of a luteinized follicle in four women with no evidence of ovulation. One of these women had estradiol and progesterone levels suggestive of ovulation, but no corpus luteum was seen. Almost all women had very low mucus scores, which did not correlate with E 2 levels. Discussion: Despite a transient increase in E 2 levels after mifepristone, there was no evidence of subsequent ovulation irrespective of whether they also received EE. The mechanism by which mifepristone in the presence of etonogestrel results in a rapid increase in E 2 levels remains unclear and could not be related to any significant changes in FSH, LH, ovarian follicle dynamics or subsequent possible ovulation. Conclusion: Pregnancy is very unlikely to occur if mifepristone and EE are given during use of Implanon to stop an episode of bleeding. © 2011 Elsevier Inc. All rights reserved.